Sintesis dan Karakterisasi Nanosilika dari Limbah Silica Scaling PLTP Dieng Melalui Metode Alkali Fusion NaOH - Waziz, Wildan; Riko Aulia , Rachman; Fajar , Fitriani (Indonesian Journal Publisher, 2024)
Silica scaling is the main problem that arises in the operation of geothermal power plants (PLTP) in Dieng. Silica scaling can disrupt electricity production and cause a buildup of waste in the environment. Silica scaling has a high silica (SiO2) content so it has the potential to be used as a value-added material, namely nanosilica. One method to obtain nanosilica is alkali fusion. This research aims to obtain nanosilica from silica scaling waste from PLTP Dieng using the alkali fusion method as well as knowing the characteristics of the nanosilica produced. The alkali fusion process is carried out using NaOH as an alkali source. Then mixing silica scaling powder and NaOH at varying temperatures of 600°C, 650°C and 700°C to produce nanosilica. The resulting nanosilica was then characterized to confirm the success of the synthesis process in producing nanosilica particles. The characterization carried out included x-ray diffraction (XRD) to characterize crystallinity, Fourier transform infrared (FTIR) to characterize functional groups, transmission electron microscope (TEM) and particle size analyzer (PSA) to determine particle size. The results of this research showed that amorphous nanosilica was successfully synthesized from silica scaling using the NaOH alkali fusion method. It was found from the results of TEM and PSA characterization that the smallest particle size was produced at a fusion temperature of 650°C. Furthermore, FTIR data also confirms the existence of functional groups at wave numbers identical to silica.